Measurement of Noise that Effect Neonatal in an Incubator Room - علي, كنانه (Latakia University Journal -Engineering Sciences Series, 2021)
The Incubator is an environment filled with people and equipment with acoustic alarms. Exposure to noise in the Incubators rooms has the potential to affect neonatal auditory development, increased respiratory and heart rates, heightened blood pressure and increased stress. The aim of this study was to measure acoustic noise levels in Incubators rooms and to improve the acoustic environment inside incubators room that we studied. We will try to identify the linear parameters of sound and how to measure noise inside one of the incubators rooms in a Hospital. In order to determine level of sound –inside the room- during different periods of time and many cases. This will help us to find out the noisiest places, sources of noise and comparing the values with the standards recommended by the American Academy of Pediatrics (AAP) to protect neonatal and staff from effects of noise. We started from a group of recent studies, Noise levels were measured in Incubators rooms with a sound-level meter .These values are higher than recommended by AAP. Significantly, most of the noise was human-generated, so we had to highlight the need to develop awareness of the negative effects of noise in the incubators rooms and to implement programmers to reduce noise.